Characterization, adsorption, and electrokinetic properties of modified sepiolite - Beyli, Pınar Turan; Doğan, Mehmet; Alkan, Mahir; Türkyılmaz, Aydın; Turhan, Yasemin; Demirbaş, Özkan; Namlı, Hilmi (Elsevier BV, 2015)
AbstractThe metal ion adsorption and electrokinetic properties of sepiolite modified by 3-(trimetoxysilyl)propyl metaacrylate was studied. The characterization of modified sepiolite was made by Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), scanning electron micrograph (SEM), and differential thermal analysis/thermogravimetry (DTA/TG). The adsorption behavior of Fe(III), Mn(II), Co(II), Zn(II), Cu(II), and Cd(II) metal ions on modified sepiolite from aqueous solutions was investigated as a function of equilibrium pH, temperature, and ionic strength. The adsorption experiments were carried out using a batch method. The initial and final concentrations of heavy metals were determined by means of atomic absorption spectrophotometry. The zeta potential of the modified sepiolite suspensions was measured as a function of metal ion concentration and equilibrium pH using a Zeta Meter 3.0. The results showed that the amount of adsorbed metal ions increased with solution pH, and tha...
Keywords: Metal Ions; Characterization; Zeta Potential; Modified Sepiolite; Adsorption